Museum Purbakala Bumiayu sebagai Media Pembelajaran Kontekstual Berbasis Religius di Sekolah Dasar - Arifin, Muh Luqman; Mukrodin; Pertiwi, Amelia Khana; Ida, Yuhdiyati Nur; Jinan, Tsalwa Diyaul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This community service activity aims to develop and implement a religious-based contextual learning model by utilizing local potential, namely the Bumiayu Archaeological Museum in Brebes Regency, Central Java, as a learning medium in elementary schools. The program was carried out through collaboration between the community service team of Peradaban University and SD Islam Ta'allumul Huda Bumiayu, with a focus on developing learning modules and media entitled